The location determinants and timing of FDI: an empirical analysis of pharmaceutical firms' FDI in China - Jiang, Fuming (Academy of International Business and Economics, 2004)
This study investigated how the location factors at sub-country level affected operation location decisions in the context of international pharmaceutical firms' FDI in China during the period of 1980-1998. It also performed a comparative analysis between early and late entrants on the decision. The results suggested that the stage of a region's economic development in China had the most significant influence on international pharmaceutical firms' decision on the choice of operation location within China. Joint ventures' FDI location decisions were heavily dependent on the region where the Chinese partner was located. Infrastructure and Chinese government's incentive policy in the region also attracted significant attention from international investors. Effectiveness of energy supply, the purchasing power in the region, quality of marketing infrastructure, land cost, local customs, and historical/traditional connections/linkages between the regions and foreign investors had a moderate influence on international pharmaceutical firms' FDI destination within the country. The research also revealed that the incentive policies provided by the Chinese government for a particular region, the stages of economic development in a region, and the availability of infrastructure had a stronger influence on early entrants' decision in selecting an operation location in China.